Aphrodisiac Effects of Areca Fruit in Erectile Dysfunction Rat Model - Nita Parisa; Muhammad Totong Kamaluddin; Salni Salni (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2019)
Abstract. Erectile Dysfunction (ED) cases are quite high in both women and men and increase with age. Areca fruit, ginseng and purwoceng are plants that have been traditionally used to increase male vitality. This in vivo experimental research study with pre and post-test control group design located in the laboratory of animal house and the biomolecular laboratory Faculty of Medicine Sriwijaya University. The subjects of this study were albino rats (Rattus norvegicus), Wistar strains, divided into 6 groups are negative control, Sildenafil, Areca Fruit Extract (AFE) 50 mg/kgBW, AFE 100 mg/kgBW, Combination of Areca Fruit, Ginseng and Purwoceng (AGP) 50 mg/kgBW and AGP 100 mg/kgBW. Female rat was injected by giving 500 mg/100 g of subcutaneous progesterone and 10 Î¼g/100 g of BB benzoate 48 hours before mating so that female mice enter the esterus phase. In this study it was found that Combination of Areca fruit, Ginseng and Purwoceng (AGP) group 50mg/kgBW significantly improved testosterone levels compared to sildenafil, while single areca fruit (AFE) dose 50mg/kgBW increased FSH and LH levels as well as sildenafil statistically. Keywords: areca fruit, erectile dysfunction, FSH, ginseng, LH, purwoceng, testosteron.